2000
DOI: 10.1103/physreve.62.1234
|View full text |Cite
|
Sign up to set email alerts
|

Threshold of induced transparency in the relativistic interaction of an electromagnetic wave with overdense plasmas

Abstract: An exact analytical investigation of the stationary solutions describing the interaction between high-intensity laser radiation and an overdense plasma is presented. Both the relativistic and striction nonlinearities are taken into account, and their joint action gives rise to a solitary solution. This solution clearly shows that there exists an inherent limit of the induced transparency on the density of the overdense plasma in order to obtain a stationary physical solution. Furthermore, it is found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 19 publications
12
113
1
Order By: Relevance
“…The threshold for HB RPA is in very good agreement with Cattani's prediction for the penetration threshold of such pulses. 18 We have also shown that longer laser wavelengths might be exploited to reach higher energies. At a laser wavelength of 1 lm and I % 1 Â 10 21 W cm À2 one can produce proton bunches with average proton energies up to about 70 MeV via HB RPA, at 2 lm this becomes 125 MeV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The threshold for HB RPA is in very good agreement with Cattani's prediction for the penetration threshold of such pulses. 18 We have also shown that longer laser wavelengths might be exploited to reach higher energies. At a laser wavelength of 1 lm and I % 1 Â 10 21 W cm À2 one can produce proton bunches with average proton energies up to about 70 MeV via HB RPA, at 2 lm this becomes 125 MeV.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a thick target, as we are concerned with here, it was predicted, by Cattani et al, 18 that penetration of a laser pulse will be prevented by compression of electrons at a density somewhat lower than the relativistically corrected critical density. The expression given in Ref.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In such concept the effect of plasma Coulomb field in self-induced transparency is ignored, which instead became recently a topic of intense research [19][20][21][22][23]. The ponderomotive force pushes the electrons deep into the target in the form of a moving electron density spike and produces a charge separation layer (a cavity in a realistic 3D geometry) extending from the target's edge to the laser pulse front.…”
Section: Gwangju 61005 Koreamentioning
confidence: 99%